2011
DOI: 10.1016/j.mvr.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of gC1qR/p33, a receptor for C1q, inhibits adherence of Staphylococcus aureus to the microvascular endothelium

Abstract: Endovascular infections with Staphylococcus aureus (S. aureus) are associated with high mortality. gC1qR/p33 (gC1qR), a receptor for the complement component C1q expressed on endothelial cells, interacts with protein A of S. aureus and gC1qR blockade reduces S. aureus colonization during infective endocarditis. The aim of this study was to analyze in vivo whether this observation is due to a decreased interaction of S. aureus with the microvascular endothelium. A dorsal skinfold chamber was prepared in Syrian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Previous work has also shown that protein A binds to the surface of platelets [32] . The data reported here is consistent with other studies where anti- gC1qR/p33 monoclonal antibodies have been shown in vivo to block S. aureus adhesion to endothelial cells treated with TNFα in a murine model, and to reduce S. aureus colonization of the aorta in a rat model of infective endocarditis [42] , [43] .…”
Section: Discussionsupporting
confidence: 92%
“…Previous work has also shown that protein A binds to the surface of platelets [32] . The data reported here is consistent with other studies where anti- gC1qR/p33 monoclonal antibodies have been shown in vivo to block S. aureus adhesion to endothelial cells treated with TNFα in a murine model, and to reduce S. aureus colonization of the aorta in a rat model of infective endocarditis [42] , [43] .…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, SG grafts have still to be considered as biocompatible, because the number of adherent leukocytes was constantly <300/mm 2 , which is far below the typical values of adherent leukocytes in severely inflamed dorsal skinfold chambers (>700/mm 2 ). 17,34,35 Moreover, both experimental groups presented with low numbers of casp-3-positive apoptotic cells in the perigraft granulation tissue, further indicating the lack of direct cytotoxic effects of the different silver coatings of IS and SG.…”
Section: Discussionmentioning
confidence: 91%
“…Inasmuch as agents that block gC1qR are likely to be useful in blocking BK generation, the gC1qR domains identified in these studies can serve as suitable templates for the design of either antibody-based or peptide-based therapeutic agents for the prevention or attenuation of vascular leakage and subsequent inflammation. This rationale is further strengthened by recent animal model studies that showed: (i) vascular permeability induced by the attack phase plasma from C1 inhibitor-deficient patients was prevented by blockade of gC1qR with mAb 74.5.2 (Bossi et al, 2009 ), and (ii) blockade of gC1qR – shown previously (Nguyen et al, 2000 ) to serve as EC and platelet receptor for protein A – inhibits adherence of S. aureus to microvascular endothelium (Sethi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 93%